Correlation of IL-10 Gene Polymorphisms and Serum Level with Hepatitis C Virus Infection in Iraq - Hassan M. Naif (Journal of Global Pharma Technology, 2020)
Hepatitis C virus (HCV) infection is a major health problem worldwide where130-150 million people are chronically infected with HCV, which progress to cirrhosis or hepatocellular carcinoma. A total of 120 subjects were recruited to assess the correlation between gene polymorphisms (IL-10-1082 and -819) with the susceptibility to HCV infection in Iraqi patients by using allele specific PCR. The serum level of IL-10 was assessed by ELISA. Gene polymorphism results of IL-10-1082A/G (rs1800896) showed significant increase in AA distribution (P=0.0076) and allele A frequency (P=0.049) among the control group while AG distribution were significantly higher in patients (P=0.0082). Although, G allele frequency had but an association (P=0.049), but the homozygous GG mutant genotype had no significant differences between the two groups. While the genotype analysis of the second SNPs of IL-10-819C/T (rs1800872) showed that neither CC nor CT genotypes distribution were associated with HCV infection (0.1627 and 0.2559, respectively) but the TT distribution and allele frequency had a suggestive association in patients (P=0.0483 and 0.0257, respectively). Results of IL-10 serum levels were higher by two-fold in patients than in healthy controls. It appeared that the IL-10-1082 AA genotype had a protective effect against HCV infection but the TT genotype of -819 mutations had a suggestive association with susceptibility to infection with HCV in Iraqi patients. Such correlation may indicate a protective role for IL-10 and could be used as a predictive risk susceptibility biomarker for progressive infection with HCV. Keywords: Hepatitis C virus, IL-10, Polymorphism, Cytokine, Iraq.